Memoirs of a clown who dared to laugh - Barbosa, Joana Marques (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This autobiographical article examines the journey of a clown–mother–researcher, addressing intersectional challenges in Brazilian female clowning. Through three key episodes—harassment during performance (2006), misogynistic audience aggression (2024), and comparisons in mixed-gender duos (2025)— it reveals how the female comic body negotiates gender stereotypes, motherhood, and structural violence. Diving into feminist theories (hooks, Iaconelli, Crenshaw) and femicide data (FBSP, 2023), the study demonstrates that clowning, traditionally a male-dominated field, imposes on women a double burden: artistic excellence and social policing. The narrative exposes issues ranging from onstage objectification to the isolation of artistic motherhood and the academic invisibility of researcher–mothers. It frames laughter as political resistance, proposing a feminist reinterpretation of the grotesque as a tool to destabilize patriarchy. The analysis particularly highlights the paradox of the red nose—symbol of freedom yet insufficient protection against gender violence; the “spectral masculinity” of absent fathers in maternal narratives; and the embodied cost of triple shifts (artist-researcher-mother). Ultimately, it celebrates clowning as a language of insurgency that exposes gender asymmetries persisting even beneath the comic disguise.